Nebulization procedures for children with unknown viral status during the COVID-19 pandemic (2020)
During the Covid19 pandemic there has been much discussion about in-hospital procedures that may generate aerosols. One such procedure, that has led to confusion and concern, is nebulisation of children. In this paper, we discuss the evidence around whether nebulisation procedures generate aerosols, and offer strategies around nebulisation of children with asthma.